2013
DOI: 10.1071/an12262
|View full text |Cite
|
Sign up to set email alerts
|

Pasture herbage mass, quality and growth in response to three whole-farmlet management systems

Abstract: Abstract.The effects of different whole-farm management systems were explored in a farmlet trial on the Northern Tablelands of New South Wales, Australia, between July 2000 and December 2006. The three systems examined were first, a moderate input farmlet with flexible grazing on eight paddocks considered 'typical' of the region (farmlet B), a second, also with flexible grazing on eight paddocks but with a high level of pasture renovation and increased soil fertility (farmlet A) and a third with the same moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 24 publications
(66 citation statements)
references
References 41 publications
1
64
1
Order By: Relevance
“…The large peaks of WEC in late spring and summer of November and December 2004 on farmlets A and B were both associated with losses of ewes with lambs with acute haemonchosis (4.7 and 5% of ewes on each of these farmlets, respectively). These results suggest that, while intensification of sheep grazing systems in the Northern Tablelands region is unlikely to provide substantial benefits in parasite control, nevertheless the higher levels of green digestible herbage provided by farmlet A (Shakhane et al 2013) enabled a substantially higher SR to be supported without incurring higher worm burdens than on farmlet B. On the other hand, farmlet C had significantly lower WEC and 8 7 6y 6x 6 5 4 3 2y 2x 2 1 8 7 6 5 4 3 2y 2x 2 1y 1x 1 17zii 17zi 17yii 17yi 17xii 17xi 17w 17 16y 16x 16 15y 15x 15 14y 14x 14 13yii 13yi 13y 13x 13 12yii 12yi 12y 12x 12 11y 11x 11 10y 10x 10 9y 9x 9 8y 8x 8 7y 7xii 7xi 7x 7 6yiii 6yii 6yi 6y 6xiii 6xii 6xi 6x 6 5yiii 5yii 5yi 5y 5x 5 4ziii 4zii ...…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…The large peaks of WEC in late spring and summer of November and December 2004 on farmlets A and B were both associated with losses of ewes with lambs with acute haemonchosis (4.7 and 5% of ewes on each of these farmlets, respectively). These results suggest that, while intensification of sheep grazing systems in the Northern Tablelands region is unlikely to provide substantial benefits in parasite control, nevertheless the higher levels of green digestible herbage provided by farmlet A (Shakhane et al 2013) enabled a substantially higher SR to be supported without incurring higher worm burdens than on farmlet B. On the other hand, farmlet C had significantly lower WEC and 8 7 6y 6x 6 5 4 3 2y 2x 2 1 8 7 6 5 4 3 2y 2x 2 1y 1x 1 17zii 17zi 17yii 17yi 17xii 17xi 17w 17 16y 16x 16 15y 15x 15 14y 14x 14 13yii 13yi 13y 13x 13 12yii 12yi 12y 12x 12 11y 11x 11 10y 10x 10 9y 9x 9 8y 8x 8 7y 7xii 7xi 7x 7 6yiii 6yii 6yi 6y 6xiii 6xii 6xi 6x 6 5yiii 5yii 5yi 5y 5x 5 4ziii 4zii ...…”
Section: Discussionmentioning
confidence: 90%
“…The improved level of control of worms on farmlet C was associated with significantly increased susceptibility to worm infection (Colvin et al 2012) and reduced animal productivity as shown by reduced liveweights (Hinch et al 2013a) and fat scores (Hinch et al 2013b) of livestock on this farmlet relative to those on farmlets A and B. The long rest periods and lower levels of soil fertility on farmlet C were found to be associated with lower levels of both legume and pasture digestibility within this farmlet (Shakhane et al 2013) and these are likely to have contributed to the reduced productivity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The climate experienced during the trial taught researchers a lot about the climatic realities of this area such as the frequent dry periods ) and the occasional bursts of pasture growth that were so short-lived that it was difficult to measure their effects (Shakhane et al 2013a).…”
Section: Reflections From the Researchers And Extension Specialistsmentioning
confidence: 99%
“…Also of great interest to them were the importance of maintaining the legume component of pastures (Shakhane et al 2013a) as a source of protein needed for meat ) and wool products (Cottle et al 2013); the significant differences observed between farmlets, in spite of the years being relatively dry; and the challenges of getting sown pastures to persist long enough to be worthwhile investments (Behrendt et al 2013a).…”
Section: Reflections From the Livestock Producersmentioning
confidence: 99%